Teaching ecological principles as a basis for understanding environmental issues - Paul Webb; Gill Boltt (Environmental Association of Southern Africa, 1989)
In this study an abstract food web and ecological case study data were used to determine high school pupils' and university students' ability to predict possible outcomes of interactions between populations within a community. Present data indicate that the majority of respondents could predict interactive outcomes within a food web if they were simple enough to be answered using strategies based on the food chain concept, but most respondents were unable to predict probable outcomes when the effects of a change in one population within a community are spread along multiple routes. Almost all the pupils and students could reorganise population data into satisfactory tables and graphs, but less than 50% of the respondents could integrate clues and predict outcomes acceptably. Data provided by three respondent age groups suggest that if clear conceptual development regarding interactions between populations does not take place at school level, misconceptions are likely to persist among first year university students. Also, the poor quality of answers given by respondents indicates that explicit teaching, prior to the use of such exercises, may greatly enhance their value. It is suggested that, by asking pupils to forecast events from supplied data, one is making explicit one of the implicit, applied reasons for studying ecological processes, i.e., conservation and management.